Prostate bed irradiation with alternative radio-oncological approaches (PAROS): a prospective, multicenter and randomized phase III trial - Körber, Stefan A.; Katayama, Sonja; Sander, Anja; Jäkel, Cornelia; Häfner, Matthias; Debus, Jürgen; Herfarth, Klaus (Radiation oncology, 2019)
For patients with treatment-naïve carcinoma of the prostate, hypofractionated irradiation becomes more and more popular. Due to the low α/β value of prostate cancer, increased single dose leading to a shortened treatment period seems to be safe and feasible. However, reliable data is lacking for post-prostatectomy patients so far. Further, the role of proton therapy is still under debate. Two prospective phase II trials with both, hypofractionated photon and proton therapy, provided promising results.
Gesehen am 01.10.2019